Peningkatan Hasil Belajar Matematika menggunakan Model Pembelajaran Make a Match Berbantuan Media Magic Ball - Sari, Anita; Widayati, Sri; Sri Legowo, Yogi Ageng (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2024)
To improve students' mathematics learning outcomes in building materials, teachers require the application of interesting learning models and media. In an effort to achieve this goal, researchers will apply the Make a Match learning model assisted by Magic Ball Learning Media so that students are more interested in learning activities. The type of research used by researchers is classroom action research (PTK) which consists of 2 cycles with data collection techniques through test results. The results of the research through the application of the Make A Match learning model assisted by Magic Ball Learning Media showed an increase in classical achievement of KKM (70) by 94% in cycle 2, which means this research was declared successful.Keywords: learning outcomes, Make A Match, Magic Ball